Pierre Robin sequence with a novel mutation in SOX9 gene: Case study - Mohd Murtaza; Md Niamat Ali; Mahrukh Hameed Zargar (Elsevier, 2021)
Background: Pierre Robin Syndrome (PRS) is a rare congenital anomaly characterized by micrognathia, glossoptosis, and cleft palate. The PRS has been found to be associated with the cleft palate with the incidence of 1/8500 to 1/14000 births. Case characteristic: We reported a case of a four-day-old male neonate without any familial history of congenital anomalies. The proband was having a symptom of micrognathia and glossoptosis with a concern of feeding and respiration. Outcomes: Molecular analysis was performed by extraction of the DNA followed by the polymerase chain reactions and sequencing of the SOX9 gene. During the analysis of the sequence, c.448C > A mutation was found in exon 1 of the SOX9 gene. The parents were found to be heterozygous, while the proband was found to be homozygous. This mutation (c.448C > A) in exon 1 of the SOX9 gene leads to a change in triplet codon from CCG to ACG at position 150 (p. Pro150Thr). Conclusion: The results of this study showed a positive association, suggesting that the gene SOX9 has a role to play. Although the genetic etiology of PRS is not clearly understood. The SOX9 gene codes for the SOX9 protein that controls the proper development of the facial structure. Thus, we hypothesized that PRS in this proband was caused by the haploinsufficiency of the SOX9 gene.